Perceived quality of parent-child interaction in parents of autistic children: relationship with parental education level - Wang, Feiying; Du, Wenchong; Iao, Lai-Sang (Frontiers in Psychiatry, 2024)
Introduction Most autism research was conducted in Western, Educated, Industrialised, Rich and Democratic (WEIRD) countries. This study is the first to examine factors that were associated with perceived quality of parent-child interaction in non-WEIRD parents of autistic children. Methods Ninety-one Chinese parents of autistic children (82 females, 9 males) completed an online survey which involved two sections. The first section included demographics questions about the parent and the family, including age, gender, educational level, and household income. It also assessed parents’ perceived quality of parent-child interaction and their autistic traits. The second section included demographics questions about their autistic child, including age and gender, and assessed autistic traits and behavioural problems. Results Parent’s education level was associated with and the only predictor of their perceived quality of parent-child interaction. The higher educational level in parents the higher quality of parent-child interaction was perceived by the parents. Discussion These findings underscored the significance of parents’ education level as a unique predictor of perceived parent-child interaction quality among Chinese parents of autistic children, providing implications to corresponding education and social policies in China and other non-WEIRD countries.